AKURASI PERAMALAN BEBAN LISTRIK SEKTOR RUMAH TANGGA MENGGUNAKAN ARTIFICIAL NEURAL NETWORK DI KOTA PALANGKA RAYA - Mahendra Penyarikan, I Gede; Dyana Arjana, I Gede; Arta wijaya, I Wayan (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUM, 2024)
Electrical energy is one of the most important energies in the daily life of the people of Palangkaraya, both in business, social, government and household sects. Planning electrical energy in its needs is needed to avoid an energy crisis, because economic growth in the Palangkaraya City area requires electrical energy in its operations. The planning carried out in the study by predicting electricity demand used the ANN (Artificial Neural Network) method. ANN is used at the prediction stage within the scope of the household sector. JST results have good forecasting accuracy with MAPE (Mean Absolute Percentage Error) of 7.1975%. With an absolute error value occurred at Rates of R.2/3,500VA to 5,500VA in July amounting to 32.2728%.